Population inversion in a single InGaAs quantum dot using the method of adiabatic rapid passage - EASTHAM, PAUL (My University, 2011)
Preparation of a speci c quantum state is a required step for a variety of proposed practical uses of quantum dynamics. We report an experimental demonstration of optical quantum state preparation in a semiconductor quantum dot with electrical readout, which contrasts with earlier work based on Rabi opping in that the method is robust with respect to variation in the optical coupling. We use adiabatic rapid passage, which is capable of inverting single dots to a speci ed upper level. We demonstrate that when the pulse power exceeds a threshold for inversion, the nal state is independent of power. This provides a new
PUBLISHED
Keywords: Condensed matter physics; semiconductor quantum dot; Nanoscience & Materials; Telecommunications